Robotic Process Automation with Automation Anywhere Techniques to Fuel Business Productivity and Intelligent Automation Using RPA. - Mahey, Husan (Packt Publishing, Limited, 2020)
This book will help you get you up to speed with developing performant software robots to automate business processes. With the help of examples, practical case studies, and step-by-step instructions, you'll be able to make the most of Automation Anywhere for building RPA solutions.